POLA ASUH DEMOKRATIS DALAM MEMBANGUN PERILAKU ANAK (STUDI KASUS DI DESA BATUAN KABUPATEN SUMENEP) - Alvi Rahmatillah; Iskandar Dzulkarnain (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2023)
The purpose of this study was to determine and describe how democratic parenting in building behavior in children. The theory used in this study is the theory of achievement motivation proposed by David McClelland. McClelland's theory of achievement motivation explains that individual behavior can be influenced by three needs, namely the need for achievement, the need for power and the need for affiliation. The research method used is qualitative and case study approach. The results of this study indicate that first: There are five methods used by parents in educating their children, namely educating by example, educating with habits, educating with advice, educating with love and care, and educating children with punishment. Second: Factors that can influence children's behavior are the family environment, school environment and community environment. Third: Parents have control and control over children's behavior and are responsible for children and can control and prevent deviant behavior in children